Pusat Penelitian Dan Pengembangan Sagu Di Selatpanjang Dengan Pendekatan Arsitektur Pesisir - Agus Alfinanda; Yohannes Firzal; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Meranti islands has a huge potential of sago. Sago becomes one of the alternative foods in Indonesia. Unfortunately, there is a limited space to do a further research on sago. To facilitate the research and development of sago in Meranti islands, it is necessary to do a better design towards the Puslitbang Sago in Selatpanjang. Puslitbang design applies the Coastal Architecture Design, which has a contextual theme that sees the local elements from the surroundings. The design parts are on the typology of the roof, walls, layout and orientation of coastal house. The concept used in this building design is tual sago. Tual is a piece of sago stalk brought from the sago plantation. Being carried on the river, sea or canal, this tual is tied one by one to make a sago bond. This concept is applied based on the function of Research and Development Center as in the management, laboratories and other supporting activities.Keywordrs : Coast Architecture, Development, Research.